Micronutrient management in sandy soils through organic materials enriched with multi-micronutrients - Singaravel R.; Arthi M.; Kamaraj S.; Seenivasan M. (E3S Web of Conferences)
Deficiencies of micronutrients are more common in sandy soil due to single grain structure, low organic matter, and exchange reaction. The process of fortification of organic matter with micronutrients increases the fertilizer use efficiency. A field investigation was carried out, with organic materials fortified with micronutrients viz., Fe, Zn, and B on the micronutrients availability, and productivity of groundnut in sandy soils. The soil was Taxonomically classified as Typic udipsamments. The content of organic carbon was 0.32 percent and the status of micronutrients was below the critical limits. The treatments evaluated were T1- NPK (Control), T2- NPK + ZnSO4 @ 25 kg /ha+ FeSO4 @ 50 kg /ha+ Borax @ 10 kg/ ha, T3- NPK + Multi micronutrients fortified FYM @ 125 %, T4- NPK + Multi micronutrients fortified FYM @ 150 %, T5- NPK + Multi micronutrients fortified coirpith @ 125 %, T6- NPK + Multi micronutrients fortified coir pith @ 150 %. The study was conducted in RBD design using 3 replications with groundnut Variety TMV-3. The study proved that the application of all the micronutrients fortified organic materials was efficient in increasing the availability and uptake of micronutrients for groundnuts. Among the treatments, micronutrients fortified composted coir pith @ 125 and 150 percent were equally efficacious in improving the soil nutrient availability, yield, and nutrient uptake. A significantly higher DTPA- Fe (3.35 mg /kg) and DTPA-Zn (0.89 mg/kg) were recorded in the micronutrient-enriched coir pith manure treatment. This treatment also accounted for a significantly higher pod and haulm yield of 1855 and 2535 kg ha-1 respectively. A significant improvement in soil fertility in terms of increased availability of micronutrients and organic carbon status was also recorded with micronutrient-fortified organic manure treatments over control.